Surviving the Antarctic Winter—Life Stage Cold Tolerance and Ice Entrapment Survival in The Invasive Chironomid Midge Eretmoptera murphyi - Bartlett, Jesamine C; Convey, Peter; Hayward, Scott A L (Insects, 2020)
Keywords: Antarktis; fjærmygg; insektfysiologi; invasjonsbiologi; kuldeeksponering; kuldetoleranse; mikroklima; overvintring; termiske terskler; zoologi

The first men on the last continent – Carsten Egeberg Borchgrevink and the Southern Cross expedition, 1898 -1900 - Smelror, Morten (Fram forum, 2013)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Kapp Adare; Southern Cross; Victoria Land; ekspedisjonen; ekspedisjoner; første landgang; geologi; oppdagelsesreiser; overvintring

Belgica in the Arctic - Kjær, Kjell-G. (Polar Record, 2005)
Belgica, which Adrien de Gerlache used on the first expedition to winter in the Antarctic, was originally a bottlenose whaler named Patria, built in Norway in 1884. She was designed and constructed by Johan Chr. Jakobsen, renowned for his design of polar ships. Patria was sold to Adrien de Gerlache and renamed Belgica in 1896. In 1896–97 she was refitted and equipped in Sandefjord, Norway, for an Antarctic expedition. Nansen and Amundsen met for the first time on Belgica's deck. Late in 1899 Belgica returned to Antwerp after more than two years on an Antarctic expedition. From 1901 to 1904 Belgica returned to bottlenose whaling and, in addition, made a voyage to northeast Greenland to establish depots and build houses for the Baldwin-Ziegler Polar Expedition. In 1905 the Duc d'Orléans chartered her to survey the coast of northeast Greenland, and on her return he bought her. In 1907 and 1909 she sailed on Arctic expeditions led by the Duc d'Orléans and captained by de Gerlache. In 1916 she was sold to Det Norske Kulsyndikat and renamed Isfjord. She became a freighter carrying coal from Longyearbyen to ports in northern Norway. In 1918 she was sold and her new owner converted her into a floating cod-liver oil refinery and fish-processing plant. In 1940 she was impounded by British forces and used as a floating ammunition depot. On 19 May 1940 she was sunk during a German air raid. Her wreck was re-discovered in 1990.
Keywords: Antarktis; Belgica (skip); Belgica ekspedisjon; Roald Amundsen; overvintring; polarekspedisjoner; polarområdene

Man in extreme environments - Brubakk, Alf O. (Aviation, space, and environmental medicine, 2000)
Humans have demonstrated the ability to live and work in many adverse environments. Many examples demonstrate that our understanding of humans ability to adapt to extreme environments is limited, but it is reasonable to assume that the main problems in space exploration will be psychological and social. It is argued that polar expeditions of an earlier age are a better model for space exploration than confinement studies or Antarctic overwintering. Some aspects of the reason for the success of these expeditions are discussed and the lessons that can be used are pointed out.
Keywords: Antarktis; fysiologi; overvintring; polarekspedisjoner; polarområdene

Johan Koren : feltzoolog og polar-pioner - Wikan, Steinar (Schibsted, 2000)
EN NORSK FELTZOOLOG OG POLAR-PIONER 17 år gammel drar snekkerlærlingen JOHAN KOREN ut fra hjembyen i Fredrikstad i 1897 som deltager i historiens første overvintringekspedisjon i Antarktis, Belgica-ekspedisjonen. Styrmann om bord er en landsmann, den unge Roald Amundsen. I likhet med ham, blir Koren snart kjent og omtalt som en av tidenes dristigste oppdagelsesreisende, med Antarktis og Arktis som virkefelt. Men for Koren blir berømmelsen ikke varig. Bare 39 år gammel dør han i spanskesyken, alene på et hospital i Vladivostok. Og med tiden går det slik at han blir "Gutten Norge glemte" - slik tittelen lød på en senere guttebok, inspirert av hans begivenhetsrike og dramatiske liv. Blant feltzoologer regnes han imidlertid den dag i dag som en pionerskikkelse, og rundt om i verdens zoologiske museer finnes tusenvis av vitnesbyrd om hans innsats for vitenskapen som samler av fugle- og dyrearter. Forfatteren, historikeren og biologen STEINAR WIKAN bygger denne beretningen på Johan Korens delvis bevarte dagbøker, samtlige brev, dokumenter og presseomtaler, erindringsbøker og - ikke minst - samtaler med en gammel mann i det fjerneste Sibir som kjente Koren.
Keywords: Antarktis; Belgica ekspedisjon; biografier; forskning; oppdagelser; overvintring; polarekspedisjoner; zoologi